A selected review of abstracts from the 11th Congress of the European Association of Neuro-Oncology (EANO). (January 2015) - Chamberlain, Marc C
SUMMARY : The European Association of Neuro-Oncology (EANO) is the largest neuro-oncology meeting in Europe that meets biannually and reproducibly provides an exciting forum to present new brain cancer clinical trials and research data. The EANO 2014 meeting in Turin, Italy (9–12 October 2014) was comprised of 3 days of presentation, nearly 50 oral presentations and nearly 350 abstracts provides a contemporary overview of neuro-oncology that includes both metastatic diseases of the CNS as well as primary brain tumors. This summary attempts to highlight select abstracts presented at the meeting of EANO 2014 in a short review that provides a portrait of a large and multifaceted meeting.